(untitled) (Journal of Engineering, 2013)
Recently, Social Sustainability has gained significant value as it was considered by the late studies as a principal dimension along with the environmental and economic sustainability. And because of, on the other hand, the significant social role of the school for forming the student’s personality, this research is an appeal for rehabilitating and promoting Iraqi Schools according the issue of social sustainability.As there is no evaluation for the Iraqi Schools, the research is dedicated to this problem, aiming to carry out the stated evaluation and define the design treatments needed for the rehabilitation process. To achieve this goal, a theoretical background for the concept of social sustainability, its criteria, the school and its social functions was introduced. From reviewing previous architectural practices and theoretical studies, different design treatments were extracted and structured within the level of the building itself and the outside landscape. The design treatments were, then, applied to rehabilitate a selected standard school model used by the Directorate of Education in Nineveh Governorate. Evaluating the proposed model, the conclusions demonstrated the possibility of rehabilitating the existing Iraqi Schools to hold most indicators of social sustainability